Peer support in language learning: Mitigating anxiety, enhancing achievement, cultivating growth mindsets, and increasing enjoyment (Journal of Applied Learning and Teaching, 2024)
This research focuses on Iranian undergraduate students and examines the impact of peer support on anxiety, success, growth mindsets, and enjoyment of learning English as a foreign language. This study employed a sequential exploratory mixed-methods approach to examine the impact of language learning interventions through peer-support on students’ experiences and outcomes. The research involved 54 monolingual Persian-speaking participants aged 18 to 20, who were randomly assigned to either the experimental or control groups. In contrast to the control group, who participated in more conventional, teacher-led sessions without peer assistance, the experimental group could rely on classmates for help in and out of class. Methods for data collection included teacher-made assessments, observations, and semi-structured interviews. Quantitative data was analyzed using independent samples t-tests, while qualitative data was analyzed using thematic analysis. Results indicated that students in the experimental group experienced lower anxiety, better academic performance, cultivated growth mindsets, and enjoyed their language learning compared to the control group. The findings emphasize the significance of peer support in establishing conducive learning environments to enhance language learning outcomes and experiences.